(3MGTjI cfR GdYQaGfs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdUdGI Ydi eMeO hBdg CLeYjf hHYO agPg LedI eG Ydi MGTjI cfR GdYQaGf s
(3BNQgG (B:s
(3hjaJbQ Pdc Gdghi hjSLO dg GdUhQI GdQGHYI dhUdi GdChdi ejbGJkG aj GdWgGQI s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1517s
Keywords: (3GdJaSjQ hYdhe GdbQBfs